(untitled) (Global Journal of Management and Business Research, 2020)
The purpose of this paper was to investigate the determinants of banking stability in European countries. This study used a sample of 280 commercial banks in 26 European Banks from 2002-2019. The bank stability most common measure is the insolvency risk (Z-Score). We used the GMM estimator technique described by Arellano and Bover (1995) to estimate the impact of bank specific and macroeconomic variables on European bank stability across different European regions by subdividing the original sample into five subsamples